The global distribution of thermospheric odd nitrogen for solstice conditions during solar cycle minimum - Gerard, J.-C.; Roble, R. G.; Rusch, D. W.; Stewart, A. I. (1984)
A two-dimensional model of odd nitrogen in the thermosphere and upper mesosphere is described. The global distributions of nitric oxide and atomic nitrogen are calculated for the solstice period for quiet and moderate magnetic activity during the solar minimum period. The effect of thermospheric transport by winds is investigated along with the importance of particle-induced ionization in the auroral zones. The results are compared with rocket and satellite measurements, and the sensitivity of the model to eddy diffusion and neutral winds is investigated. Downward fluxes of NO into the mesosphere are given, and their importance for stratospheric ozone is discussed. The results show that the summer-to-winter pole meridional circulation transports both NO and N(S-4) across the solar terminator into the polar night region where there is a downward vertical transport toward the mesosphere. The model shows that odd nitrogen densities at high winter latitudes are entirely controlled by particle precipitation and transport processes.